Determination Analysis of House Units Selling Price at Citra Kencana Residential, Bogor City - Fachriandi, Muhamad; Rulhendri, Rulhendri; Alimuddin, Alimuddin; Syaja'ah, Siti Kholifah (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
The need of people to live in continue to increase from year to year. Statistical data stated that the backlog figure (shortage of houses) in 2014 reached 15 million. One of the areas that is being developed to be used as a residential area is Tanah Sareal District, Bogor City. It is located only 30 minutes from Bogor City Hall. With a very strategic location, the developer adjusts the type of house to be built in accordance with the facilities and advantages of the Tanah Sareal area to become a luxury but affordable cluster type of housing. In preparation for this final project, the author took a case study of a Citra Kencana Residential Area, located on Kencana Village, Tanah Sareal District, Bogor City. The construction of this housing is carried out in two stages. In the first phase to be built is the Amarossa type (36/72) with a total of 5 units and a Rossalia type (40/72) with a total of 17 units. Based on the results of the analysis, the selling price of a house that matches the demand curve for the Amarossa type is Rp. 2,896,025,813.00 and for the Rossalia type is Rp.2,627,957,575.00. Assuming a margin of 10%, the price of an Amarossa type house is Rp.3,185,628,394.00 and the price of a Rossalia type house is Rp. 2,890,753,332.00. From the income diagram, it is known that the income of people who are interested in buying a house is between fifteen and twenty million per month. So that the number of monthly installments for fifteen years for the Amarossa type is Rp. 13,237,451.00. and for Rossalia type houses Rp. 12,044,805.00. Then the price that has been set above is stated in accordance with the buyer's income.